2018
DOI: 10.1051/matecconf/201822903011
|View full text |Cite
|
Sign up to set email alerts
|

Landslides induced by slaking of geomaterial

Abstract: The geological event that happens because of an unbalance between shear strength and shear stress on rock mass is known as a landslide. This usually occurs due to improper handling of the exposed material. The landslide occurs because of the reaction to reduce the burden it bears so that the mass of the rock will move rock mass from the higher elevation to lower elevation. Many landslides, in west java, Indonesia occurred on exposed clay shale that is protected by soldier pile with 3m in distance between pile.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…From Table 3, the results also indicated that water had a significant role in determining the interface failure, where a higher degree of saturation would lower the interface shear strength. Although [16] argued that a higher degree of saturation would give higher interface shear strength of clay interface with concrete, other studies agreed with the current study's results [1][2][3]. Thus, water could be concluded to reduce the interface shear strength dominantly.…”
Section: Thin-soil Interface Soil Model Results Plotted Against Labor...supporting
confidence: 85%
See 1 more Smart Citation
“…From Table 3, the results also indicated that water had a significant role in determining the interface failure, where a higher degree of saturation would lower the interface shear strength. Although [16] argued that a higher degree of saturation would give higher interface shear strength of clay interface with concrete, other studies agreed with the current study's results [1][2][3]. Thus, water could be concluded to reduce the interface shear strength dominantly.…”
Section: Thin-soil Interface Soil Model Results Plotted Against Labor...supporting
confidence: 85%
“…Due to weathering, the initial properties of clay shale would change through the degradation of the structure [1]. The degradation of clay shale would further degrade its shear strength, which led to slope instability [2,3]. Various clay shale slope analyses indicated a typical translational failure plane.…”
mentioning
confidence: 99%
“…Based on [10], it conducted a study and field survey that some clay shales in West Java, Indonesia, push some soldier piles and cause a wall collapse. This phenomenon triggers the wall at the toe part and landslide the road, and the culvert breaks, severed by seepage and indicating that the water influences durability.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding physical properties to durability, Zhang et al (2021) stated that the high intensity of rock's wet and dry cycle will affect the decrease of physical properties such as porosity, density, and fracture toughness. Oktaviani et al (2018) conducted a study and field survey that some clay shales in West Java, Indonesia, push some soldier piles and cause a wall collapse. This phenomenon triggers the wall at the toe part and landslide the road, and the culvert breaks, severed by seepage and indicating that the water influences durability.…”
Section: Introductionmentioning
confidence: 99%